The role of green brand trust, awareness, and preference in the relationship between green marketing and green brand loyalty: The case of Mobile phone brands. - Vo, Ta Thanh Minh; Vu, Quang Minh; Ha, Nguyen Tan Tai; Nguyen, Thi Quynh Mai; Truong, Bich Phuong (Journal of Finance - Marketing Research, 2025)
As environmental pollution and climate change worsen, consumers are increasingly expecting eco-friendly products and expect companies to exhibit a genuine commitment to sustainability through strategic green marketing. Modern consumers require brands to cultivate green trust by implementing tangible and credible environmental policies, thereby reinforcing awareness of sustainable values, enhancing green brand preference, and fostering loyalty. This study explores the relationship between green marketing and green brand loyalty, with green brand trust, awareness, and preference serving as mediating variables. Data were collected from a survey of 340 consumers in Ho Chi Minh City who showed interest in the green marketing practices of mobile phone brands. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the study finds that green brand trust, awareness, and preference fully mediate the influence of green marketing on green brand loyalty. These findings suggest that mobile phone brands in Ho Chi Minh City should strategically refine their green marketing approaches to build trust, raise awareness, and strengthen consumer preference, thereby enhancing brand loyalty and securing a competitive edge in an increasingly sustainability-conscious market.